Pengujian Perangkat Lunak itworkforceindonesia.org - Tiur Gantini; Yenni M Djajalaksana; Saron K Yefta (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
ITWORKFORCE is an application that built a base on the website using PHP and javascript programming language, MySQL database in 2015 and will continue to develop until hosting in 2017. This application is an application that has features regarding news, job recruitment, and surveys. For this occasion, the limitation of use concerns about the competence of the information technology field. In this study, the application test with functional testing the application of the black box method. The results show that this application has been running and can use. Hopefully this application can give a positive impact on the public, and specifically for data collection on competency in information technology in Indonesia.